Are dragons and tigers catching up? - Olesia Kozlova; Jose Noguera-Santaella (Asian Development Bank Institute (ADBI), 2017)
This paper studies the catching-up process in per capita income of the so-called Asian Dragons and Tigers. It contributes to the literature in several ways. First, it tests the catching-up hypothesis using the longest time span ever considered, from 1870 to 2014. Second, it documents the experiences of these two groups of countries and provides potential explanations for them. Third, by using the Kejriwal and Perron (2010) algorithm, we are able to endogenously estimate multiple structural breaks in the level and the trend of the series without prior knowledge of their integration level. This surpasses technical concerns of previous empirical studies. Fourth, it inquires into how the Asian financial crisis affected the catching-up process among the Dragons' and Tigers' economies.
Keywords: C22; O11; O55; 330; catching up; structural breaks; Asian Dragons; Asian Tigers